2020
DOI: 10.1016/j.jid.2019.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Potential Therapeutic Targets for Cutaneous Squamous Cell Carcinoma

Abstract: We performed a small interfering RNA screen to identify targets for cutaneous squamous cell carcinoma (cSCC) therapy in the ubiquitin/ubiquitin-like system. We provide evidence for selective anti-cSCC activity of knockdown of the E3 ubiquitin ligase MARCH4, the ATPase p97/VCP, the deubiquitinating enzyme USP8, the cullin-RING ligase (CRL) 4 substrate receptor CDT2/DTL, and components of the anaphase-promoting complex/ cyclosome (APC/C). Specifically attenuating CRL4 CDT2 by CDT2 knockdown can be more potent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…McHugh et al (2020) evaluated the effect of VCP/p97 on the viability of three squamous cell carcinoma (cSCC)cell lines (SCCRDEB4, SCCRDEBMet, and SCCTMet) compared to two normal skin cell lines (NHF and NHK) and reported that VCPsiRNAs killed cSCC cells but not normal skin cells. Cell death caused by VCP depletion was attenuated by the suppression of proteins involved in the response to the accumulation of unfolded proteins in the ER (ATF6, IRE1a/JNK1, and PKR/eiF2α) and amino acid depletion (GCN2/eiF2α) [ 116 ].…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…McHugh et al (2020) evaluated the effect of VCP/p97 on the viability of three squamous cell carcinoma (cSCC)cell lines (SCCRDEB4, SCCRDEBMet, and SCCTMet) compared to two normal skin cell lines (NHF and NHK) and reported that VCPsiRNAs killed cSCC cells but not normal skin cells. Cell death caused by VCP depletion was attenuated by the suppression of proteins involved in the response to the accumulation of unfolded proteins in the ER (ATF6, IRE1a/JNK1, and PKR/eiF2α) and amino acid depletion (GCN2/eiF2α) [ 116 ].…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
“…Thus, VCP/p97 represents a potential prognostic biomarker and a therapeutic target. [71] Gastric cancer greater tumor size, presence of vascular and lymphatic invasion, lymph node metastasis, and shorter overall and disease free survival [72] cell survival, degradation of cellular regulators, and gastric carcinogenesis [73,74] low levels of CHOP and DR5 [75] Esophageal cancer higher frequencies of lymph node metastasis, deeper invasion, metastasis, and shorter disease free and overall survival [76] shorter overall survival [77] Breast cancer shorter overall survival [78] poor outcomes of triple-negative patients receiving chemotherapy [79,80] Hematological cancer tumor grade, stage, histological subtype, recurrence and shorter overall and disease-free survival of patients with B-cell lymphoma [104] multiple myeloma development and progression [105] poor prednisone responders in pediatric patients with acute lymphoblastic leukemia [106] exosome generation and secretion in Jurkat tumor cells [107] Melanoma advanced radiotherapy [108] immune escape [109] Glioblastoma radiosensitivity of glioblastoma cells, and survival time of xenografted mice with radiation treatment [110,111] HDAC6 levels and temozolomide resistance therapy [112] Ovarian cancer chemotherapy response in patients receiving the platinum-taxane combination [113] Testicular cancer development of different types of human testicular tumors [114] Bladder cancer shorter survival following bladder removal by cystectomy [115] Squamous cell carcinoma development of squamous cell carcinoma [116] 3.1. VCP/p97 in Gastrointestinal Cancers 3.1.1.…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
“…6,7 Ubiquitination is one of the most important histone modifications and has been reported to be involved in the progress of GC frequently. 8,9 As a member of the deubiquitinating enzymes (DUBs) family, USP8 has been proved to be closely related to the occurrence and development of tumors, 10,11 including breast cancer, 12,13 lung cancer, 14 bladder cancer, 15 cervical cancer, 16 etc. USP8 was originally identified as a growth regulated ubiquitinspecific protease and is like many other DUBs characterized by its multidomain architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The genomic profile of human SCCs has revealed that many CRL-related genes are subjected to cancer-associated genetic alterations, which include gene amplification, deletion and mutation [47]. Remarkably, the anti-tumorigenic action of the neddylation pathway inhibitor MLN4924 in various SCC subtypes clearly illustrates the critical role of CRLs activity in promoting and sustaining SCC pathogenesis [85][86][87]. In line with this, the expression signature of a subset of CRL-related genes defines HNSCC with unfavorable prognosis.…”
Section: Crls and Scc Etiologymentioning
confidence: 86%